Surface activation of atomically thin metal nitride by confined nanoclusters to trigger pH-universal hydrogen evolution - Do, Viet-Hung (2023)
Transition metal nitrides hold great potential for electrochemical conversion by virtue of metal-like electrical conductivity and robust electrochemical stability. Their applications, however, are still limited due to the sluggish kinetics stemming from the unfavorable surface electron properties. Herein, we demonstrate that the confinement of atomically thin Os nanoclusters onto 2D δ-MoN can favorably optimize the surface electron configurations, thereby boosting the material's catalytic performance. MoN-5% Os catalyst with optimal Os loading exhibits high catalytic performance, surpassing that of commercial Pt/C. The enhanced hydrogen evolution performance is attributed to (1) the unique 2D atomically thin nanoarchitecture exposing abundant active sites and (2) the strong electronic interaction between Os nanoclusters and δ-MoN nanosheets, which favorably modulates the surface microenvironment. Theoretical investigation reveals that the confined Os nanoclusters function as surface activators, efficiently modulating the electron properties of MoN, thereby accelerating the sluggish water adsorption and dissociation processes and triggering favorable hydrogen adsorption.